2016
DOI: 10.1111/liv.13188
|View full text |Cite
|
Sign up to set email alerts
|

Serum WFA+‐M2BP levels for evaluation of early stages of liver fibrosis in patients with chronic hepatitis B virus infection

Abstract: WFA -M2BP is an accurate serum indicator for assessing early stages of liver fibrosis and may monitor regression of fibrosis during the treatment of chronic HBV infection. WFA -M2BP provides a simple and reliable alternative or complementary method to liver biopsy and FibroScan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
100
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(108 citation statements)
references
References 38 publications
8
100
0
Order By: Relevance
“…M2BPGi is secreted by hepatic stellate cells and have been shown to correlate with liver fibrosis in a variety of chronic liver diseases including viral hepatitis, non‐alcoholic fatty liver disease, biliary cirrhosis, and autoimmune hepatitis . Consistent with prior studies, our study also showed that M2BPGi levels were higher in CHB patients with cirrhosis than those without.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…M2BPGi is secreted by hepatic stellate cells and have been shown to correlate with liver fibrosis in a variety of chronic liver diseases including viral hepatitis, non‐alcoholic fatty liver disease, biliary cirrhosis, and autoimmune hepatitis . Consistent with prior studies, our study also showed that M2BPGi levels were higher in CHB patients with cirrhosis than those without.…”
Section: Discussionsupporting
confidence: 91%
“…In another recent study, serial M2BPGi levels after therapy were examined. The mean M2BPGi also decreased from 3.1 COI at baseline to 1.9 COI at 48 weeks and 1.5 COI at 96 weeks; however, this study only included 89 patients with serial serum samples, analysed patients with and those without cirrhosis together, and did not evaluate correlation between M2BPGi with HCC development.…”
Section: Discussionmentioning
confidence: 96%
“…Mac‐2‐binding protein glycosylation isomer (M2BPGi), a glyco‐biomarker, was firstly reported by Kuno et al as a novel biomarker in assessing the liver fibrosis severity in chronic hepatitis patients . Subsequently, studies reported that M2BPGi level might be a noninvasive marker for the assessment of liver fibrosis in patients with chronic hepatitis C (CHC), CHB, nonalcoholic fatty liver disease (NAFLD), autoimmune hepatitis (AIH), and primary biliary cirrhosis (PBC) . Recently, Nishikawa et al found that pretreatment M2BPGi level might be a useful predictor for HBeAg loss or seroconversion for HBeAg‐positive CHB patients that received the treatment of nucleoside/nucleotide analogs (NUCs) .…”
Section: Introductionmentioning
confidence: 99%
“…However, there were only six patients with HBV infection in the former study, and the cohort of the latter study consisted of HCV‐related compensated LC, while in China HBV infection is the most common etiology for LC. We have demonstrated the role of WFA + ‐M2BP for evaluating early‐stage liver fibrosis in patients with HBV infection in a previous study . In the present study, Spearman's rank correlation test showed a highest rho value between WFA + ‐M2BP and Child–Pugh classification, and ROC analysis showed a high AUROC for WFA + ‐M2BP in assessing Child–Pugh classification in patients with HBV infection.…”
Section: Discussionmentioning
confidence: 99%